PENGARUH PERBEDAAN KOMPOSISI MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL SAYURAN SAWI (Brassica juncea L.) - Paula C. H. Supit; Stella M. Th. Tulung; Sofia ., Demmassabu (Universitas Sam Ratulangi, 2022)
Mustard (Brassica juncea L.) is a horticultural plant that acts as a source of vitamins and minerals. For this reason, mustard cultivation needs to be developed. The development of mustard cultivation can be done through the selection of the right planting media to support the growth of vegetable crops, especially on limited land. This study aims to study the effect of differences in the composition of the growing media on the growth and yield of mustard greens. The study was arranged in a completely randomized design consisting of four treatments. The treatment consisted of media: A = soil; B = soil + manure (1:1); C = soil + manure + compost (1 : 1 : 1); D = soil + manure + sand (1 : 1: 1). Each treatment was repeated four times to obtain 16 experimental pots. Variables observed: Plant height (measured 2 and 4 weeks after transplanting seedlings), Number of leaves (measured 2 and 4 weeks after transplanting seedlings), Wet weight of mustard greens (weighed at harvest). The data were analyzed using analysis of variance and if there was an effect of treatment, it was continued by using the BNT test at the 5% test level. The results showed that the planting medium given manure gave the best growth and yield of mustard greens. The composition of the planting media, soil + manure + compost (1 : 1: 1) is good for the cultivation of mustard plants.